JENIS ANTHOPODA DAN KELIMPAHANNYA PADA LAHAN TANAMAN JAGUNG (Zea Mays L.) DIKAMPUNG MURAMSARI - Paskalis ighom; joana mendes; Jefri Sembiring; Nurhaya J Panga (Musamus University, 2022)
ABSTRACT A certain condition, the abundance of anthropods needed to be information for the application of integrated pest management. The abuudance anthropods obbserveddd using a yellow trap and hole trap. The research was conducted from April until Agustus 2019 for six times with an interval of two weeks. The result show that the abundance of anthropods found is 140 individuals such us of 2 classes,wich are insect class (128 individuals) and Arachnids class (12 individuals). Ordo identification in the insect class found to 6 orders which are Lepidoptera, Orthoptera, Coleoptera, Hymenoptera, Homoptera, and Diptera. The high total individuals found were of Lepidoptera orders,in 47 individuals and perform as pests, while order individuals were predators, pollinators, and decomposers. The level of diversity value of 1.42 and an abundance of 100% while the diversity value of the Arachnida class is 0 with an abundance value of 1%. Keywords : Abundance,insect,Arahchninds